Analisis Rekrutmen ASN PPPK Fungsional Guru pada Instansi Daerah - Debby Putri Pratama; Roni Ekha Putera; Hendri Koeswara (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is to find out how the PPPK recruitment mechanism for teacher formation in 2021 and whether the PPPK recruitment for teacher can meet the need of theachers and also ended the polemic of honorary teachers that has been happening in Indonesia. This research uses qualitaive approach with descriptive method. The data was collected through the process of observation and documentation. Data collection techniques are through literasi studies and documents analysis in form of government regulations, mass media news and other related documents. The result of this research are the government seems to be forced the applicants, especially from honorary staff, to become PPPK through competency exams that are repeated three times. The number of formations that aren’t filled due to lack of formation enthusiasts because these formations are located in remote areas causes imbalance number of teachers in one area with another. From the budget perspective, the lower standard of honorary salaries can encourage local governments to continue recruiting honorary workers rather than recruiting first aid teachers. The recruitment of PPPK teachers also creates new problems for private schools that are in danger of losing teachers because most of the teachers who pass the PPPK are qualified teachers.